The Influence of Coffee Husk Ash as a Filler on the Performance of Bituminous Concrete Mix - Amare Tilahun Tessema; Getachew Asefa Alene; Natnael Melsew Wolelaw (Advances in Materials Science and Engineering)
Utilization of agricultural waste by-products in road construction has become a common practice in developing countries. The present study investigates the effect of coffee husk ash compared to basaltic stone dust on the performance of bituminous concrete mixes for road construction. Based on the Marshall mix design, a total of thirty (30) asphalt concrete specimens were prepared with basaltic stone dust and coffee husk ash as a filler with bitumen content between 4.0% and 6.0% at varying increments of 0.5%, and the Marshall stability test was performed on full mixes to determine the optimum asphalt content of the mixtures. From the test results, it is seen that specimens made with coffee husk ash and basaltic stone dust are found to have satisfactory Marshall properties, and moisture susceptibility shows that mixes using CHA filler provide better resistance to moisture effects than mixtures using BSD filler. When compared to BSD, the CHA shows an 8.43% increase in OBC. From the laboratory results, it has been shown that specimens made with coffee husk ash and basaltic stone dust are found to satisfy Marshall parameters and indirect tensile strength of bituminous concrete mixes when the coffee husk ash exhibits better performance than basaltic stone dust, which indicates that the CHA shows an increase of 35.80% compared to basaltic stone dust. The research findings indicated that the TSR of the paving mixes using basaltic stone dust was 94.58% and that using coffee husk ash was 105.03%, where both fillers satisfy the minimum limiting value of 80%. Overall, using coffee husk ash as a filler in hot mix asphalt concrete helps to solve a significant agricultural waste disposal issue while also being environmentally friendly.